Institutional Quality and Economic Crises: Legal Origin Theory versus Colonial Strategy Theory - Du, Julan (The Review of Economics and Statistics, 2010)
In a natural experiment among former colonies between 1970 and 1999, weak institutions reflected in high settler mortality and French legal origin often increase the likelihood and intensity of local currency and real crises (i.e., those resulting in a drop in real output) amid six global crises. The effects of institutions on crises are often mediated through macroeconomic policies, but they are often not primary channels. Persistent institutions (i.e., those reflected in the legal origins and settler mortality) predict the occurrence and intensity of crises better than time-varying institutions do.